Some Results on Generalized Derivations of BH-Algebras - Ganesan, P.; Kandaraj, N. (Communications in Mathematics and Applications, 2021)
In this paper, we study the notion of generalized derivations on BH-algebras and investigate simple, interesting and elegant results.
Keywords: BH-algebras; BH-Sub algebras; Regular generalized derivations on BH-algebras